Deep water masses in the Iceland Basin during the Last Interglacial (MIS 5e): Evidence from benthic foraminiferal data - Nadezhda P. Lukashina; Leyla D. Bashirova (Oceanologia, 2015)
The Last Interglacial period, marine isotope stage (MIS) 5e, is a potential analogue for the Holocene. In this study, we investigated a marine sediment core, AMK-4442, recovered from the northern part of the Iceland Basin. The multiproxy approach used in this study, which includes foraminiferal and lithological analyses, identifies the difference in intensity of deep circulation between MIS 5e and the Holocene. Our data indicate that during early MIS 5e, the Iceland-Scotland Overflow Water (ISOW) flux into the Iceland Basin was suppressed. We suggest that the less active North Atlantic Deep Water (NADW) formation at this time was related to the obstruction of warm surface water inflow into the Nordic Seas.